Intelektualec v postintelektualni dobi - Vidmar, Ksenija H. (Javnost (Ljubljana), 2013)
The rise of anti-intellectual sentiment in contemporary society demands a critical refl ection and intervention. First, it needs to be asked about historical and social circumstances which have led to the explicitly negative attitude towards the intellectuals which includes both a doubt of their social role as well as historical meaning. In the introduction, the author addresses this question from a brief comparative-historical view at the age of modernity and its demise in the neoliberal rationalisation of knowledge. She takes classic text of MaxWeber on science as vocation as the starting point where, as she argues, Weber already outlines the reconsideration of the meaning of science and scientists-intellectuals after modernity. Webers contribution is then upgraded through Marxs theory of value whichin late capitalism is applied also to the sphere of intellectual labour. In conclusion, the author underlines that in the 21st century, critical social intervention can only be eff ective if linked to postcolonial and transnational aspects of intellectual work.
Keywords: javnost; intelektualci